Net zero portfolio targets for development finance institutions: challenges and solutions - Fankhauser, S; Srivastav, S; Sundvor, I; Hirmer, S; Shrimali, G (Wiley, 2023)
Development finance needs to be better aligned with climate change objectives, and many experts see net zero portfolio targets as a powerful way to achieve this. This paper explores the operational implications of net zero portfolio targets for development finance institutions (DFIs). We set out an agenda to move development finance towards net zero goals in a way that acknowledges development concerns. These include (1) setting context-specific emissions pathways with granular bottom-up data and emphasising climate-development win-wins; (2) dealing with inertia and lumpiness in the portfolio through ‘when’ flexibility (multiyear carbon budgets) and ‘where’ flexibility (sharing of carbon space); (3) encouraging transition projects through future-emissions accounting and transition credits; (4) managing climate-development and other trade-offs with an internal carbon price and ESG standards; and (5) accounting for emissions after project-end with monitoring and legal provisions.